Knowledge, Attitudes, And Access To Information Related To The Prevention Practices During The Covid-19 Pandemic (A study to undergraduate students of Public Health Diponegoro University) - Laura Respati Denta Elygio; Bagoes Widjanarko; Novia Handayani (Journal of Public Health for Tropical and Coastal Region, 2020)
Background: Health protocols of COVID-19 prevention need to be applied to suppress the cases. However, the application requires good understanding that has never been studied before, especially among public health students of Diponegoro University. Therefore, this study investigated the knowledge, attitudes, and access to information towards prevention of COVID-19 pandemicMethods: This type of research was descriptive analytic with quantitative approach, and cross sectional research design with a sample of 100 respondents (student from Faculty of Public Health Diponegoro University) selected by using probability sampling. The instrument used was an online questionnaire. Data analysis used is univariate and bivariate with chi-square testResults: The results showed that the respondent's age was dominated by age ≥ 20 years (63%) with the gender mostly female (85%). Knowledge (p = 0.015), attitude (p = 0.013), and access to information (p = 0.000) were related to the practice of Public Health student in preventing COVID-19. Besides, access to information has a significant relation with the prevention practices and internet particularly social media is the source of information most accessed by student (89%).Conclusion: It is necessary to increase Public Health student awareness, mainly about the dangers of COVID-19, avoiding misinformation, and there required to be more surveillance for personal activities and communities that have the potential to be exposed to COVID-19.